1980
DOI: 10.2307/1541013
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific and Intraspecific Acrorhagial Aggressive Behavior Among Sea Anemones: A Recognition of Self and Not-Self

Abstract: iiolot/ical Science. Floriilii Slute ['nii'crsity, 'I'ulliiliussci'. Florida 32306 Coelenterates have long been considered primitive or simple animals. Although some aspects have heen known for a long time, coelenterate behavior and its physiological and morphological bases are still poorly understood. Studies have now

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
77
0
2

Year Published

1982
1982
1997
1997

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 23 publications
0
77
0
2
Order By: Relevance
“…This argument is only partly valid. Where both types of aggression are mediated by the same 'sensor-effector systems' (nematocysts and their sensors; Buss et al 1984), the distinction between competition and predation is arbitrary (Bigger 1980, Lubbock 1980. For example, scyphistomae may well cannibalize planulae and ephyrae because they use the same sensor-effectors in both predatory and competitive interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This argument is only partly valid. Where both types of aggression are mediated by the same 'sensor-effector systems' (nematocysts and their sensors; Buss et al 1984), the distinction between competition and predation is arbitrary (Bigger 1980, Lubbock 1980. For example, scyphistomae may well cannibalize planulae and ephyrae because they use the same sensor-effectors in both predatory and competitive interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies of competitive aggression among benthic hydrozoans have found extremely 'fine-tuned' sensory discrimination at both interspecific and intraspecific levels (reviewed by Buss et al 1984, Grosberg 1988: hydroids are able to identify genetically distinct colonies as nonself and to compete with them, whether or not the compehtor is of the same or another species. The effectors in these interactions are nematocysts , and the sensory discrimination is genetically based (Ivker 1972, Bigger 1980, Buss e t al. 1984, McFadden e t al.…”
Section: Introductionmentioning
confidence: 99%
“…When such anemones make physical contact with one another, usually with their tentacles, after initial tentacle withdrawals, if the anemones do not perceive each other as inert objects and if they are unable to avoid further contact with one another (e.g., by bending or releasing their pedal discs from the substrates and passively floating away), an acrorhagial attack takes place (Abel, 1954;Bigger, 1980Bigger, , 1988Bonnin, 1964;Brace, 1981;Brace and Pavey, 1978;Francis, 1973). After making contact, the acrorhagi expand and are repeatedly applied to the target organism.…”
Section: Chemoreception In Coelenterates Backgroundmentioning
confidence: 99%
“…Acrorhagi have two morphologically and functionally separate regions: the distal tip and the peduncle (Bigger, 1980(Bigger, , 1982Doumenc, 1972;Sebbins, 1984). In Anthopleura and Bunodostorna, the receptors that initiate the behav- ioral response and the subsequent ectodermal peeling are located at the tip; only the distal tip produces a peel (Bigger, 1976(Bigger, , 1980(Bigger, ,1982.…”
Section: Chemoreceptors In the Anthozoa (Sea Anemones And Corals) Seamentioning
confidence: 99%
“…Immune recognition is widespread in invertebrates (1), and allograft rejection has been described in ascidians (2,3), earthworms (4,5), molluscs (6), coelenterates (7)(8)(9), sponges (10), echinoderms (11)(12)(13), and insects (14,15). Allogeneic reactions have also been observed in vitro with isolated cells, at least in urochordates (16), and in sponges (17)(18)(19), indicating that invertebrate allorecognition is a direct cellular response.…”
mentioning
confidence: 99%